The southern Moroccan passive continental margin: an example of differentiated long-term landscape evolution in Gondwana - Sehrt, Manuel; Glasmacher, Ulrich A. (Gondwana research, 2018)
The ENE-trending Anti-Atlas mountain belt reveals variation in recent topography with elevations of >3km indicating a differentiated long-term landscape evolution. To unravel the subsidence and exhumation history, low-temperature thermochronology has been applied on 21 samples from the Precambrian basement of the Irherm, Kerdous, Ifni, and Bas Drâa inlier. Thermochronological data suggest a common geological evolution of the western Anti-Atlas. Zircon fission-track ages from 287 (±23) to 331 (±24)Ma point to a main exhumation in the Late Carboniferous-Early Permian assigned to the Variscan folding and post-folding erosion. Zircon (U-Th)/He (205-287Ma) and apatite fission-track (120-219Ma) data are related to the Central Atlantic rift and drift stage, as the Anti-Atlas formed the exhumation shoulder of the rift system. The rock uplift and exhumation phase lasted up to the Early Cretaceous, whereby 9km of Precambrian-Palaeozoic overburden has been eroded. Thermal modelling reveals a minor sedimentary burial (1.5-2.5km) throughout the Cretaceous, in accordance with the widespread transgression across the northern Africa in the Cenomanian-Turonian. Apatite (U-Th-Sm)/He ages between 49 (±3) and 164 (±10)Ma confirm recent minor exhumation in the western Anti-Atlas with an increasing impact of the Atlasian orogeny and potentially a mantle plume anomaly from southwest to northeast reflecting the differentiated topography in the area.